Comunidades sustentáveis: autoridade e autonomia em questão - Santos, Sara Jane Escouto dos (2011)
The study on the form of organization of new social groups emerges with strength, especially, in the end of the decade of 80-90 of the 20th Century. The Sustainable Communities, recurring theme, are configured as a one-way announcement of new possibilities of peaceful coexistence, based on economic issues, either by relational issues, or personal and collective ideals. Signal and represent something that is in contemporary scene, and also as a complaint that life in society needs to offer elements of a more ecological, holistic and harmonious character. This dissertation seeks, in its central base for research, to understand how to operate the authority and autonomy within Sustainable Communities. These were the Community Sustainable Ecological Spiritual Dwelling of Peace - CMP and the Foundation Land Mirim - Center of Light - FTM - CL. The selection was performed with intentionally character , and is justified for the fact that they were spaces of social, environmental and cultural impact, with important coverage local-regionalnational, representing, in the same way, cultures and ways of living in different regions of the Country. Also been used as criteria for the choice: the time of existence of at least five years, the bond of the researcher with the communities to be investigated, the experience in the development of social, environmental and/or educational projects, with local impact, and the willingness to give access to the documents relating to their activities. Morada da Paz with its territory central in the South of Brazil and Earth Mirim in the Northeast. This research´s methodology is based on documentary analysis using as a source the institutional or personal files supplied by the two communities. It is clear that, even though they are located in different locations, and have different time of existence and cultural characteristics, they also have similar items in respect to: its content and organizational challenges experienced. Even in a different context, they experienced the same requirements and similar demands. The standpoint made possible by this experienced investigation are the contributions on the way to look at and how to input may exist to the extent that they build interfaces between the Social Work and all of its corpus methodology, with the socio-environmental manifestations of the social question, expressed in this thesis, through the study of the Sustainable Communities. Another result of the research is the need for greater production of Social Work on the socioenvironmental theme, however it stands out the learning that is in giving visibility to the dialectic be-being that exists between the social worker and be composing as part of a sustainable community and contributing to this area of proclamation and complaint that characterize it. In the research on the processes of the authority and autonomy, it identifies as central to the practice of participatory activities, with and interdisciplinary theoretical basis, universal ethical principles, with cultural and ritualistic basis, applicable to their members and to all those who interact with these communities. These practices show the validation of the legitimately constituted, from the individual and collective knowledges and practices, thus constitute autonomy on the basis of the recognition of oneself and the other.